2014
DOI: 10.1007/s00296-014-3064-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in children with juvenile idiopathic arthritis: reliability of the “Pediatric Quality of Life Inventory-Multidimensional Fatigue Scale”

Abstract: The aim of the study was (1) to translate the "Pediatric Quality of Life Inventory-Multidimensional Fatigue Scale" (PedsQL-Fatigue) into Brazilian Portuguese language and culture and evaluate its reliability and (2) to measure fatigue among patients with juvenile idiopathic arthritis (JIA): (1) Translation of the PedsQL-Fatigue by two bilingual researchers; (2) Backtranslation into English assessed by the authors of the original version; (3) Pilot study with five patients followed in the Pediatric Rheumatology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
5
0
4
Order By: Relevance
“…In our study, participants with active disease reported more fatigue compared to those in remission off medication or inactive disease. These results are in agreement with several other studies of JIA [14,46,50], and consistent with a large international study of about 10,000 RA participants [51]. Other studies found no significant association between disease activity in JIA and fatigue.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, participants with active disease reported more fatigue compared to those in remission off medication or inactive disease. These results are in agreement with several other studies of JIA [14,46,50], and consistent with a large international study of about 10,000 RA participants [51]. Other studies found no significant association between disease activity in JIA and fatigue.…”
Section: Discussionsupporting
confidence: 93%
“…However, the actual numbers are not comparable as different fatigue measurements and cut-offs were used. In contrast, a Brazilian study reported no significant differences in fatigue between children with JIA and controls [46]. This study gave limited descriptive information, making further comparisons difficult.…”
Section: Discussionmentioning
confidence: 66%
“…Unlike most studies of fatigue in patients with JIA, we also assessed fatigue symptoms and fatigue severity. We measured fatigue symptoms using a validated and disease-specific questionnaire that is commonly used in studying patients with JIA (19). Besides, we have used the most common scale to measure fatigue severity because we considered that fatigue symptoms and fatigue severity may be associated with different factors.…”
Section: Discussionmentioning
confidence: 99%
“…Fatigue symptoms were evaluated with Pediatric Quality of Life Inventory-Multidimensional Fatigue Scale (PedsQL-F). PedsQL-F is a valid and reliable tool, and it can be used to measure symptom-specific fatigue among patients with JIA (19). PedsQL-F, which is an 18-item questionnaire designed to measure the child's and the parent's perception of fatigue in pediatric patients, comprises a general fatigue scale (6 items), sleep/ rest fatigue scale (6 items), and cognitive fatigue scale (6 items).…”
Section: Evaluation Of Fatiguementioning
confidence: 99%
“…PedsQL-MFS foi traduzida e adaptada culturalmente para língua portuguesa do Brasil(PAULO et al, 2015). Como ocorreu no nosso estudo, não se verificaram maiores dificuldades na compreensão dos itens.…”
unclassified